Trajectory tracking sliding mode control for underactuated autonomous underwater vehicles with time delays. (7th May 2020) - Zhou, Jiajia; Zhao, Xinyi; Feng, Zhiguang; Wu, Di
Trajectory tracking control of autonomous underwater vehicles in three-dimension always suffers disturbances such as input time delays and model uncertainties. Regarding this problem, an integral time-delay sliding mode control law is proposed in this article with dividing the vehicle's input time delays model into cascade system consisting of a kinematics subsystem and a dynamics subsystem. Based on the established pose error equation and velocity error equation, a suitable Lyapunov–Krasovskii functional is given to analyze and guarantee the global stability of the whole system under reasonable assumptions. At last, comparative simulations are presented to demonstrate the effectiveness of the proposed method.